Screening method of lowland rice genotypes for zinc uptake efficiency (Scientia Agricola, 2001)
Zinc deficiency in crop plants has been recognized as a worldwide nutritional constraint. A greenhouse experiment was conducted with the objective of developing a screening technique to evaluate lowland rice genotypes for zinc use efficiency. Ten lowland (Oryza sativa L.) genotypes were tested at low (0 mg Zn kg-1) and high (10 mg Zn kg-1) zinc levels applied to an Inceptisol. Genotypes differed significantly in grain yield and its components. Based on the grain yield efficiency index, genotypes were classified as efficient and inefficient. The most Zn efficient genotypes were: Metica 1, Epagri 108, CNA 7550, and CNA 8619. The most inefficient genotype was CNA 8319. The moderately efficient genotypes were: Javae, Rio Formoso, CNA 7556, and CNA 7857. The screening method used for Zn use efficiency is simple and does not require plant analysis. This methodology can be used for crop genotype evaluation of mineral stresses, which have direct bearings in genetic studies and breeding programes